2017
DOI: 10.1590/1519-6984.01916
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of freshwater decapods in an Atlantic rainforest catchment with a dammed future

Abstract: Variations in physical characteristics along the course of a river influence habitat availability which reflects in species distribution. Knowledge of ecology and diversity of lotic species is important for evaluating how river ecosystems will respond to environmental impacts. Freshwater decapods are a group of high ecological and economic importance, but the knowledge about factors influencing their distribution is scarce in Brazil. We performed a survey of decapods to describe their abundance and distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although fish communities have been found to be strongly associated with woody material (Wright & Flecker, 2004; Chua et al, 2020), this relationship is not significant for Macrobrachium species. This suggests a greater reliance of Macrobrachium on leaf litter microhabitats for foraging and refuge (Crowl et al, 2001; March et al, 2001; Silva‐Junior, Silva‐Araújo & Moulton, 2017) and highlights the importance of a diverse array of microhabitats for aquatic biodiversity in general.…”
Section: Discussionmentioning
confidence: 99%
“…Although fish communities have been found to be strongly associated with woody material (Wright & Flecker, 2004; Chua et al, 2020), this relationship is not significant for Macrobrachium species. This suggests a greater reliance of Macrobrachium on leaf litter microhabitats for foraging and refuge (Crowl et al, 2001; March et al, 2001; Silva‐Junior, Silva‐Araújo & Moulton, 2017) and highlights the importance of a diverse array of microhabitats for aquatic biodiversity in general.…”
Section: Discussionmentioning
confidence: 99%
“…Hazeri et al (2019) reported that crustacean species depend on the availability of habitat structure. In detail, Silva-Junior et al (2017) reported that decapods were more abundant in leaf litter substrates than in sandy areas. In the Logawa River, leaf litter substrate was predicted to have originated from the tributary before Station II and the stream before Stations IV, V, and VI ( Figure 1).…”
Section: Longitudinal Distributionmentioning
confidence: 99%